2013
DOI: 10.1620/tjem.230.75
|View full text |Cite
|
Sign up to set email alerts
|

A Human Thyroid Cancer Cell Line, DH-14-3, Newly Established from Poorly Differentiated Thyroid Carcinoma

Abstract: Poorly differentiated thyroid carcinoma (PDTC) is a newly recognized histological type of malignant thyroid tumor, accounting for about 2 -13% of all thyroid carcinomas. PDTC is considered as a morphologically and biologically intermediate stage between well-differentiated thyroid carcinoma and anaplastic thyroid carcinoma. PDTC preferentially manifests bone metastases. We here established a cell line from a resected tumor specimen from a 70-year-old male patient with PDTC who presented with multiple bone meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Proteins encoded by MMP and MT-MMP genes can alter cell-cell and cell-ECM junctions; both mediate the release and activation of autocrine or paracrine signaling molecules such as angiogenic activators as well as activate or deactivate cell surface receptors, promoting invasiveness and metastasis [ 34 ]. On the other hand, matrix metalloproteinase-1 may be responsible for the aggressiveness or bone metastasis of poorly differentiated thyroid carcinoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins encoded by MMP and MT-MMP genes can alter cell-cell and cell-ECM junctions; both mediate the release and activation of autocrine or paracrine signaling molecules such as angiogenic activators as well as activate or deactivate cell surface receptors, promoting invasiveness and metastasis [ 34 ]. On the other hand, matrix metalloproteinase-1 may be responsible for the aggressiveness or bone metastasis of poorly differentiated thyroid carcinoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, depletion of APE/Ref-1 also resulted in evident attenuation of cell invasiveness, possibly mediated by decreased activities of MMP-1 and Snail. MMP-1 was considered to be closely associated with tumor aggressiveness, metastatic potential and poor prognosis ( 26 – 29 ). Specifically, MMP-1 expression is largely controlled at the transcriptional level through a major enhancer element consisting of a consensus AP-1 site ( 30 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among several genes to be upregulated by RET/PTC1-mediated transformation of human thyroid cells, CXCL8 (RNA and protein) was the main upregulated gene [176]. The poorly differentiated thyroid carcinoma cell lines SMP and DH-14-3 also have high constitutive levels of CXCL8 [177]. When Bauerle et al [178] examined a panel of thyroid cancer cell lines, they found those which secreted low levels of CXCL8 were not capable of forming tumors in vivo, while the two cell lines that were highly tumorigenic (BCPAP and 8505C) secreted much higher amounts of CXCL8.…”
Section: Ccr6 Cxcr4 and Cxcl8 In Thyroid Cancermentioning
confidence: 99%